Aplicação e efetivação das decisões da corte interamericana pelo poder judiciário brasileiro em matéria de empresas e direitos humanos - Lima, Fernando Antônio de (2024)
This thesis deals with the legal relationship between companies and human rights, based on the hermeneutic standards highlighted by the Inter-American Court. The objective is to establish interpretative mechanisms that enable the Brazilian Judiciary to apply and implement the decisions and jurisprudence of the Inter-American Court, so that business activities respect and guarantee human rights. In this way, the aim is to integrate, within the Brazilian legal system, the domestic and international legal order in the protection of human rights. Through an analysis of the jurisprudence of the Inter-American Court of Human Rights, binding on Brazil, it was observed that domestic conduct and norms, related to business activities, must observe a higher parameter formed by internal and international legal elements of protection of rights human rights – particularly the international legal elements of the inter-American regional human rights system. These internal legal elements are formed by internal laws, the Federal Constitution, judicial decisions of the Federal Supreme Court. International legal elements are formed by international legal norms, practices of international organizations, decisions of the Inter-American Court of Human Rights. It is enough that these elements (internal and international) have the necessary normative force to protect and guarantee human rights. Thus, instead of constitutionality control or conventionality control, taken separately, the superior control parameters bring together internal and international normativity. Hence the proposal for control of transconstitutionality or transconventionality of domestic norms and conduct. A constitutional norm can even give rise to a domestic law or a provision of an international treaty, as long as the latter two have greater protective force for human rights. In this sense, the internal and international legal elements protective of human rights merge, in what is called, in this thesis, the theory of integrated or aggregating control. What attracts internal and international legal elements to the upper part of the system is the principle of primacy or preference of the norm most favorable to the person, provided for in art. 29 of the American Convention on Human Rights. This attraction is not abstract, but always part of the reality in which marginalized and socially vulnerable groups are inserted. The inductive method was used, observing the jurisprudence of the Inter-American Court, to formulate general laws of interpretation and application of Law, such as, for example, the theory of aggregate or integrative control and the control of transconstitutionality or transconventionality in the relationship between companies and human rights. The conclusion obtained is a new model of Legal Hermeneutics capable of combining internal and international legal elements and, thus, integrating Constitutional Law and International Human Rights Law in matters of business and human rights. This work is linked to Research Line 2 of the Postgraduate Program at Nove de Julho University, called “Transnational Company and Regulation”, with a concentration area “Transnational Companies and the Enforcement of Human Rights”.